Pelatihan dan Pendampingan Budidaya Ubi Jalar di Desa Suci dalam Rangka Mendukung Implementasi Integrated Farming: Pengabdian - Uyun Erma Malika; Rizal Perlambang CNAWP; Ahmad Haris Hasanuddin Slamet; Fairuz Nadhifah; Salihati Hanifah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The concept of integrated farming is a relevant approach to supporting sustainable agriculture in rural areas. Suci Village, Panti District, Jember Regency, has potential natural resources that support the development of an integrated farming system, particularly for sweet potatoes. However, farmers' limited knowledge and skills in applying appropriate cultivation techniques result in suboptimal production results. This community service activity aims to improve partners' knowledge and skills through training and mentoring on sweet potato cultivation to support the implementation of integrated farming. The activity method includes preparation, training, mentoring, and evaluation. The activity was carried out from July to October 2025 through lectures, focus group discussions (FGDs), and direct practice of organic sweet potato cultivation in polybags using organic fertilizer from local livestock waste. The results of the activity showed an increase in participants' understanding and skills in environmentally friendly sweet potato cultivation techniques and support the implementation of an integrated farming system in Suci Village.